Ectopic Adrenocorticotropic Hormone Syndrome in Small Cell Lung Cancer Associated with Refractory Hypokalemia: A Case Report - Elias, Koch; Rola, Nakhoul; Amir, Amara; Farber, Evgeny; Michael, Jerdev; Farid, Nakhoul; Nakhoul, Nakhoul (Archives of Clinical and Medical Case Reports, 2019)
Small cell lung cancer (SCLC) is aggressive cancer with high mortality without appropriate early treatmenr. The patient can present with paraneoplastic syndromes, such as Cushing syndrome, because of an inappropriate secretion of ectopic adrenocorticotropic hormone (ACTH) with severe hypokalemic metabolic alkalosis, Parathyroid hormone with hypercalcemia, and hyponatremia due to inappropriate anti-diuretic hormone (ADH) secretion. Patients with SCLC and paraneoplastic syndrome, are with poor prognostic factor. Diagnosis must be made early with immediate treatment. We report a 57-year-old male patient who had severe refractory hypokalemia, metabolic alkalosis, and hypertension as manifestations of an inappropriate secretion of ACTH-secreting from small cell carcinoma of the lung. He was treated with high doses of spironolactone to control the symptomatic refractory hypokalemia, and Metyrapone to control the ectopic ACTH secretion. Aggressive chemotherapy was initiated soon after lung mass biopsy, with SCLC diagnosis.